2014
DOI: 10.1007/s10147-014-0729-8
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of osteosarcoma occurring as second malignancy of childhood cancers may be favorable: experience of two cancer centers in Japan

Abstract: Attention should be paid to complications of treatment for the first childhood cancer in the treatment for osteosarcoma occurring as second malignancy. The prognosis of osteosarcoma as second malignancy of childhood cancers may be more favorable than that of conventional osteosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A later study reported that radiation-induced secondary osteosarcoma proved to have similar outcomes to primary osteosarcoma 33 . However, a recent study suggested that the prognosis of secondary osteosarcoma may be more favorable than that of primary osteosarcoma 34 . The survival and prognostic factors of secondary osteosarcoma remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A later study reported that radiation-induced secondary osteosarcoma proved to have similar outcomes to primary osteosarcoma 33 . However, a recent study suggested that the prognosis of secondary osteosarcoma may be more favorable than that of primary osteosarcoma 34 . The survival and prognostic factors of secondary osteosarcoma remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, the survival rate for osteosarcomas is only 50% to 80% despite with an intensive chemotherapy. Numerous efforts have been made to elucidate the mechanisms of osteosarcoma and to develop novel therapeutic strategies [1,2]. Cell growth and division cycle were carefully controlled in normal tissues, thereby ensuring a homeostasis of cell number and thus maintenance of normal tissue architecture and function.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, chemotherapy was administered according to the contemporary Cooperative Osteosarcoma Study Group protocols for secondary osteosarcoma (9), including surgery and multiagent chemotherapy. Furthermore, Yonemoto et al (10) reported that 7 of 9 patients (77.8%) with osteosarcoma as a secondary cancer survived without disease (mean follow-up period, 10.9 years); therefore, the prognosis of osteosarcoma occurring as a secondary malignancy following treatment for childhood cancer may be more favorable compared with that of conventional osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%